PENGEMBANGAN LKPD BERBASIS PROYEK PADA MATA PELAJARAN MATEMATIKA PEMBELAJARAN LUAS BANGUN DATAR SEDERHANA DI KELAS V SD - Anindia Husni Caniago; Nila Lestari (Sekolah Tinggi Pariwisata Mataram, 2023)
This development research was motivated by the findings of the researchers when conducting observations in class V SD 106450 Cinta Air, that the learning design was still not optimal and the delivery of learning materials was less interesting so that students experienced boredom in learning mathematics. This development research aims to develop a project-based LKPD on the subject of mathematics learning area of ​​simple flat shapes in fifth grade elementary school which is feasible to use. This research is a type of research and development using the ADDIE development model. In this study, the researcher only carried out the ADDIE development model only until the development stage, because the focus of this research was only to develop project-based worksheets on mathematics subjects learning broad simple flat shapes that were suitable for use in the learning process. The instrument used to collect data is a questionnaire or questionnaire given to 3 expert validators, namely material expert validators, language expert validators and learning expert validators. Based on the validation results from the material expert validators, a score of 98 was obtained with the